2012
DOI: 10.1007/s10745-012-9462-y
|View full text |Cite
|
Sign up to set email alerts
|

Wild Edible Plant Markets in Kisangani, Democratic Republic of Congo

Abstract: Benefits from wild edible plants (WEP) are multiple for rural households as well as urban traders. To set species priorities for WEP market development and domestication, we performed an inventory of WEP species and traders in five markets and one road-side selling point in Kisangani. During four one-month sessions between September 2007 and July 2008, all WEP traders present in the target markets were interviewed. We registered 119 unique sellers, selling 15 different WEPs. The September-October period and 'M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…When we compared our results with studies on Congolese medicinal plant use (Biloso and Lejoly 2006; Fundiko 1997; Katemo et al 2012; Makumbelo et al 2008; Mpiana et al 2007; Tabuna 1999; Termote et al 2012; www.prota4u), we found that 80% of the species we encountered in Matonge are also used as medicinal plants in Congo, while the remaining 20% are typical West African species. However, several of the most commonly sold non-food medicinal plants in Kisangani (Katemo et al 2012) and Kinshasa (Makumbelo et al 2008), two major cities in the DRC, were not found in Matonge, such as Alchornea cordifolia (Schumach.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…When we compared our results with studies on Congolese medicinal plant use (Biloso and Lejoly 2006; Fundiko 1997; Katemo et al 2012; Makumbelo et al 2008; Mpiana et al 2007; Tabuna 1999; Termote et al 2012; www.prota4u), we found that 80% of the species we encountered in Matonge are also used as medicinal plants in Congo, while the remaining 20% are typical West African species. However, several of the most commonly sold non-food medicinal plants in Kisangani (Katemo et al 2012) and Kinshasa (Makumbelo et al 2008), two major cities in the DRC, were not found in Matonge, such as Alchornea cordifolia (Schumach.…”
Section: Discussionmentioning
confidence: 77%
“…The popularity of aphrodisiac plants is also known from West African (Quiroz et al 2014; Van Andel et al 2012) and Central African markets (Biloso and Lejoly 2006; Termote et al 2012a; Towns et al 2014) and the Afro-Caribbean (Van Andel et al 2012b), where these bitter tonics are regarded as a part of one’s manliness and cultural identity rather than just as treatments for impotence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Locally important forest products contribute significantly to livelihoods not only for rural people, but also in urban and peri-urban environments where intermediaries and traders of NWFPs often come from poorer and more marginalized sectors of society [77][78][79]. In many cases, traders carry out useful marketing functions such as risk taking and transport, which can be costly.…”
Section: Marketing and Value Chains Integrating Forest Foodsmentioning
confidence: 99%
“…Foods other than wild yams are also important sources of macro-and micronutrients and energy for millions of people in the Congo Basin. Enquiries conducted in different regions in Cameroon [26,75,[87][88][89][90], Côte d'Ivoire [91] and in the Democratic Republic of Congo [92,93] revealed the high proportion of WEP fruits and seeds. The importance of fruits or seeds is linked to their high nutritive value and also to the production and long-term storage of derived products (oils for example).…”
Section: Discussionmentioning
confidence: 99%